2018
DOI: 10.2298/abs180423028j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticancer and antimicrobial activities of the Polygonum maritimum ethanol extract

Abstract: Polygonum maritimum is a traditional herbal remedy that produces abundant flavonoid secondary metabolites. The ethanol extract of P. maritimum aerial parts (POM) was chemically characterized and tested for antimicrobial properties and cytotoxicity. Results of LC-MS/MS analysis showed high contents of gallic acid, epigallocatechin gallate and catechin, and significant amounts of quercetin-3-O-galactoside and quercetin-3-O-glucoside. Evaluation of the antifungal properties revealed that POM induced notable growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In this study, we examined in vitro cytotoxic properties of POA and PEA, alone and combined with commercial cytostatic D. Our investigation provided corroborative evidence that POA and PEA extract could potentiate D cytotoxicity in hepatocarcinoma (HepG2) cells. This result is in accordance with our previous findings [28], which demonstrated a synergistic interaction between Polygonum maritimum extract and D in HepG2 cells. Likewise, Ghazali et al [48] demonstrated that herb extracts obtained from Polygonum minus have an antiproliferative effect on HepG2 cells.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, we examined in vitro cytotoxic properties of POA and PEA, alone and combined with commercial cytostatic D. Our investigation provided corroborative evidence that POA and PEA extract could potentiate D cytotoxicity in hepatocarcinoma (HepG2) cells. This result is in accordance with our previous findings [28], which demonstrated a synergistic interaction between Polygonum maritimum extract and D in HepG2 cells. Likewise, Ghazali et al [48] demonstrated that herb extracts obtained from Polygonum minus have an antiproliferative effect on HepG2 cells.…”
Section: Discussionsupporting
confidence: 94%
“…The cytotoxic effects of plant extracts and D, both as single compounds and in a mixture, were assessed by MTT assay, as described by Jovanović et al [28]. HepG2 cells were seeded into 96-well plates at a density 2 × 10 4 cells/well and incubated overnight with 5% CO 2 at 37 • C. Further on, the cells were exposed to a series of two-fold dilutions of extracts and D in the ranges 4000-125 µg/mL and 22.8-0.712 µg/mL, respectively.…”
Section: Cytotoxicity and Drug Synergism Analysismentioning
confidence: 99%
“…The cytotoxic effect of supernatants of probiotic yogurts enriched with APF on HCT 116 and SW-620 were tested in parallel with control yogurts without APF and WE (initial stock 100 mg/mL), using an MTT assay as described [26]. The assay was performed after 24 h-long exposure of the cells to diluted supernatants of yogurt with 20% APF and control yogurt as well as diluted WE (50 mg/mL).…”
Section: Cell Culture Maintenance and Cytotoxicity Assaymentioning
confidence: 99%
“…Normal human lung fibroblast cells MRC-5 (ECACC 84101801, UK) were cultured in DMEM supplemented with 10% FBS and 1% penicillin-streptomycin mixture at 37 • C. The cytotoxic effects of the plants' extracts were assessed by an MTT assay as previously described [37]. Briefly, MRC-5 cells were seeded into 96-well plates at a density of 4 × 10 4 cells/well and exposed to a series of twofold dilutions of the extracts (0.25-2 mg/mL) for 24 h. Following incubation, the medium was replaced with one containing MTT in a final concentration of 0.5 mg/mL, and the cells were incubated for 3 h. Then the medium was removed, the formazan crystals were dissolved in DMSO and the A 570 was measured using an Infinite ® 200 PRO (Tecan Group Ltd., Menndorf, Switzerland).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%